2021
DOI: 10.31234/osf.io/5rmvu
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Agreement Attraction in Turkish: The Case of Genitive Attractors

Abstract: Previous studies have shown that speakers may find sentences violating subject-verb agreement grammatical when the sentence contains a feature-matching noun phrase. This so-called agreement attraction effect has also been found in genitive possessive structures such as 'the teacher's brother' in Turkish (Lago et al., 2019), which is in contrast with its absence in similar constructions in English (Nicol et al., 2016). This discrepancy has been hypothesized to be a result of the association between genitive cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Let us start with number agreement attraction in comprehension in its reading times reflex. This has been documented in English (Wagers et al, 2009;Tanner et al, 2014;Parker & An, 2018), German (Lago & Felser, 2018), Turkish (Lago et al, 2019;Turk & Logačev, 2021), Spanish (Lago et al, 2015), Armenian (Avetisyan et al, 2020), Arabic (Tucker et al, 2015), French (Franck et al, 2015), and Russian (Slioussar, 2018). These studies represent a substantial amount of evidence in favour of the effect bein robust and present across different languages, which has also been supported by a meta-analysis (Jäger et al, 2017).…”
Section: Introductionmentioning
confidence: 66%
“…Let us start with number agreement attraction in comprehension in its reading times reflex. This has been documented in English (Wagers et al, 2009;Tanner et al, 2014;Parker & An, 2018), German (Lago & Felser, 2018), Turkish (Lago et al, 2019;Turk & Logačev, 2021), Spanish (Lago et al, 2015), Armenian (Avetisyan et al, 2020), Arabic (Tucker et al, 2015), French (Franck et al, 2015), and Russian (Slioussar, 2018). These studies represent a substantial amount of evidence in favour of the effect bein robust and present across different languages, which has also been supported by a meta-analysis (Jäger et al, 2017).…”
Section: Introductionmentioning
confidence: 66%
“…Additionally, Türk (2022) found fewer agreement attraction errors with genitive possessors in Turkish when the experiment included additional conditions that were less likely to give rise to agreement attraction. In the context of our 2AFC continuation task, it is possible that participants were sensitive to within-experiment statistics about whether the second noun in these constructions was activated when processing verbal agreement.…”
Section: While the Qualitative Pattern Of Accuracy Findings Mirrors T...mentioning
confidence: 86%
“…reflect differences in answering preferences occasioned by the different balance of nonsubject-like bare noun distractor/subject-like modified distractor conditions in Experiment 4. Hammerly et al (2019) and Türk (2022) show that response biases can change the qualitative pattern of agreement errors in acceptability judgment tasks (see also Laurinavichyute & von der Malsburg, 2023). Hammerly et al (2019) found that agreement attraction errors may vary with response bias, depending on whether participants expect the sentence they see to be ungrammatical to a lesser or greater extent.…”
Section: While the Qualitative Pattern Of Accuracy Findings Mirrors T...mentioning
confidence: 97%
“…There are some previous findings that indicate that overt case marking may modulate interference in the production literature (e.g., Badecker & Kuminiak, 2007;Nicol & Antón-Méndez, 2009) as well as in the comprehension literature (e.g., Slioussar, 2018) (cf. Avetisyan et al, 2020;Turk & Logacev, 2022). German has overt case marking (nominative, accusative, dative, or genitive) on determiners, nouns, and adjectives.…”
Section: The Present Eye-tracking Studymentioning
confidence: 99%